2008
DOI: 10.4314/ari.v4i1.40802
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate Fauna Of A Nigerian Freshwater Ecosystem

Abstract: A survey of macro invertebrate fauna of Anambra River was carried out for 22 months at Otuocha, Ogurugu and Nsugbe. The macro invertebrates were sampled using kick sampling techn ques and scoop nets. Sampled specimens were ident fied to generic level. During the study a total of 21 genera of macroinvertebrates belonging to 13 families were identified. The fauna was composed of Gyrinus sp. (29.2%), Macrobranchium sp. (19.6%), Ranatra sp. (13.2%) and Agabus sp. (3.5%). The margalef's index of fauna richness show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Their abundance was however low in stations 2 and 3. The oligochaeters respond to organic pollution by increase in abundance (Egborge, 1995;Eyo and Ekwonye, 1995;Odo et al, 2007). Their presence in stations 2 and 3 could be attributed to organic enrichment and growth of macrophytes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Their abundance was however low in stations 2 and 3. The oligochaeters respond to organic pollution by increase in abundance (Egborge, 1995;Eyo and Ekwonye, 1995;Odo et al, 2007). Their presence in stations 2 and 3 could be attributed to organic enrichment and growth of macrophytes.…”
Section: Discussionmentioning
confidence: 98%
“…In Nigeria, definitive information on aquaculture based on water quality parameters of lotic and lentic system is useful and many investigations have been conducted to assess the physicochemical and macroinvertebrate (Eyo and Ekwonye, 1995;Odo et al, 2007) status of aquatic ecosystems as guidelines for rational fisheries management and resource conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Anambra river is River Niger's largest tributary below Lokoja and is often considered to be a component of the lower lowlands of Niger. The river flows into the Niger river for 210 kilometers and has its source from Ankpa hills where it flows through a narrow trough in a southern direction that gradually spreads as it runs down [10]. The river has a large basin of 14,010 km 2 which is located between latitude 6°10' and 7°20', longitude 6°35' and 7°40', east of the river Niger (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…Planktonic, pelagic, and benthic organisms live in aquatic environments. Benthic macroinvertebrates and vertebrate fauna in tropical waters have shown that a quantitative collection of key species from natural aquatic habitats can help estimate ecological parameters like species richness or evenness in diversity (Odo et al, 2007). The physical and chemical properties of the water and immediate substrate of occupation determine the emergence and distribution of macroinvertebrates and vertebrates (areas of water bottom occupied by the macroinvertebrate and fish).…”
Section: Introductionmentioning
confidence: 99%